Transport properties of membrane vesicles from Acholeplasma laidlawii. III. Evidence of active nature of glucose transport - Fedotov, N S; Panchenko, L F; Tarshis, M A (Folia microbiologica, 1975)
Membrane vesicles obtained from Acholeplasma laidlawii accumulate glucose as well as maltose and fructose against their concentration gradient in the absence of exogenous energy sources. Glucose uptake by membrane vesicles is inhibited by anaerobiosis and by electron transfer inhibitors, such as rotenone and amytal, but not by 2-heptyl-4-hydroxyquinoline N-oxide, antimycin A, cyanide and azide. Rotenone, cyanide and amytal also produce a rapid efflux of glucose from the membrane vesicles. Arsenate, oligomycin and N,N'-dicyclohexylcarbodimide do not inhibit glucose transport. Transport of glucose is markedly inhibited by proton conductors such as CCCP and pentachlorophenol. It is concluded that glucose transport can be driven by a high-energy state of the membrane or by the membrane potential.
Keywords: Rotenone; anaerobióza; glukosa; maltosa; amobarbital; fruktosa; Biological Transport, Active; Sulfhydryl Reagents; sulfhydrylová reagencia; Cell Membrane; rozpřahující látky; Acholeplasma laidlawii; Maltose; chemická deprese; Fructose; Anaerobiosis; Depression, Chemical; Amobarbital; subcelulární frakce; rotenon; buněčná membrána; Uncoupling Agents; Subcellular Fractions; aktivní transport; Glucose